Custodianship on the periphery: archives, power and identity politics in post-apartheid Umbumbulu, KwaZulu-Natal - McNulty, Grant (Social Anthropology, 2016)
Since 1994, there have been significant shifts in official systems of record-keeping in South Africa. Notions of tradition and custom have been reconfigured within a legislative environment and in the province of KwaZulu-Natal, what was previously held separately as the domain of the 'tribal subject' (tradition and custom) now intersects with the domain of the democratic citizen (legislation, government records and archives). The intersection of these domains has opened up new cultural and political spaces in which the past in various forms is being actively managed. Through a study of contemporary Umbumbulu in southern KwaZulu-Natal, this thesis explores a host of custodial and record-keeping forms and practices, often in settings not conventionally associated with custodianship and archives. The study takes as its point of departure the Ulwazi Programme, a web initiative of the eThekwini Municipality that its advocates term a collaborative, online, indigenous knowledge resource. It then considers various other locations in Umbumbulu in which the past is being dealt with by certain traditional leaders and local historians such as Desmond Makhanya and Siyabonga Mkhize. The thesis argues that the activities of the subjects of the study reveal a blurred distinction between practices of custodianship and the production of versions of history and posits that they might be best described as practices of curation. Their activities show that the past, in a range of forms, is being mobilised in efforts to gain access to land and government resources, and to enter into the record marginalised historical claims and materials. Moreover, the types of knowledge that flow from their activities at a local level serve to unsettle dominant modes of knowing, including those related to custodianship, archives and identity, and they shape socio-political relations, with amongst others, the Zulu royal family and the Premier of KwaZulu-Natal. The thesis advances the argument that in contemporary KwaZulu-Natal the terms, and the act, of consignation of depositing materials in a repository, out of public circulation and with limited access an action that enables both remembering and, once preserved, the possibility of forgetting, far from being a defined, archival procedure, is a tenuous, volatile, indeed actively negotiated and navigated, process.